PARLIAMENTARISM VERSUS SEMI-PRESIDENTIALISM IN THE BALTIC STATES: THE CAUSES AND CONSEQUENCES OF DIFFERENCES IN THE CONSTITUTIONAL FRAMEWORKS - Norkus, Zenonas (Baltic Journal of Political Science, 2013)
Restoring their statehood in the early 1990s, Estonia and Latvia established parliamentary republics, while Lithuania opted for semi-presidentialism. The paper is a case-oriented comparative study explaining this difference with the Lithuanian “exceptionality” in focus. Part of the answer is differences of interwar constitutional history: while Lithuania and Estonia had to cope with the legacy of three constitutions each, Latvia inherited only the parliamentary Constitution of 1922, because its dictator Karlis Ulmanis did not bother to constitutionalize his rule. Another part is differences in the balance of power during the time of extraordinary politics when constitutions were made. The alternation between the presidential and parliamentary phases of semi-presidentialism and the “perils of presidentialism” did manifest repeatedly in the Lithuanian post-communist politics, while Estonia and Latvia did know next to nothing about them, except for the “Zatlers episode” in Latvia in 2009–2011.The infamous Rolandas Paksas’ impeachment in 2003–2004 and controversial features in the performance style of the Lithuanian president Dalia Grybauskaitė are important illustrations of the shortcomings of semi-presidentialism, which could be cured by Lithuania’s switch to the Baltic pattern of parliamentary presidency. However, as time goes on, the probability of a constitutional reform decreases in all Baltic States, mainly due to increasing acquis constitutionnel and habituation.